Solid electrolyte and preparation method and application thereof

By uniformly covering the composite coating of lithium fluoride and alumina on the surface of the halide electrolyte, a solid electrolyte with high ionic conductivity, oxidation potential and air stability was prepared, which solved the problem of poor performance of existing battery ratios. , achieving improved battery performance and reduced production cost.

CN119447435APending Publication Date: 2025-02-14ZHEJIANG INTELLIGENT TRANSPORTATION TECHNOLOGY INNOVATION CENTER +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411602735.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing lithium-ion batteries based on solid electrolytes have shortcomings in ionic conductivity, oxidation potential and air stability, resulting in poor rate performance.

Method used

采用一种包括卤化物电解质和复合包覆层的固态电解质,复合包覆层由氟化锂和氧化铝组成,质量比为(1~9):(9~1),通过原子层沉积包覆 Treatment and low temperature heat treatment preparation.

Benefits of technology

The solid electrolyte has been improved in terms of high ionic conductivity, oxidation potential and air stability, which enhances the rate charge and discharge performance of the battery, and reduces the preparation environment requirements and costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The embodiment of the invention provides a solid electrolyte and a preparation method and application thereof, and relates to the technical field of battery materials. The solid electrolyte comprises a halide electrolyte and a composite coating layer arranged on the surface of the halide electrolyte, wherein the composite coating layer comprises lithium fluoride and aluminum oxide in a mass ratio of (1-9): (9-1). The solid electrolyte has excellent ionic conductivity, oxidation potential and air stability, and is beneficial to realizing high-rate charge-discharge performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery materials, and in particular to a solid electrolyte and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have been widely used in various portable electronic products and electric vehicles. Among them, solid-state lithium-ion batteries using solid electrolytes have greater safety advantages.

[0003] In the prior art, electrolyte systems based on solid electrolytes include solid electrolyte materials such as oxides, sulfides and halides.

[0004] However, in the above-mentioned methods, the ionic conductivity of oxide electrolytes and halide electrolytes is relatively low, and the sulfide electrolytes and halide electrolytes have poor air stability, resulting in poor rate performance of the batteries used therein. Summary of the invention

[0005] The present application provides a solid electrolyte and a preparation method and application thereof. The solid electrolyte has excellent ionic conductivity, oxidation potential and air stability, which is conducive to achieving high-rate charge and discharge performance of the battery.

[0006] In a first aspect, the present application provides a solid electrolyte comprising a halide electrolyte and a composite coating layer disposed on the surface of the halide electrolyte, wherein the composite coating layer comprises lithium fluoride and aluminum oxide in a mass ratio of (1 to 9): (9 to 1).

[0007] In one possible implementation, the mass ratio of the lithium fluoride to the aluminum oxide is (1-3):(9-7).

[0008] In a possible implementation manner, the particle size of the halide electrolyte is larger than the particle size of the composite coating layer.

[0009] In a possible implementation, the particle size D50 of the halide electrolyte is (8-15) μm; and / or the particle size D50 of the composite coating layer is (0.05-1) μm.

[0010] In a possible implementation, the halide electrolyte is a monoclinic halide electrolyte.

[0011] In one possible embodiment, the chemical formula of the halide electrolyte is Li 2+x In x Zr 1-x Cl6, 0.05≤x≤0.95.

[0012] In a possible implementation manner, the mass ratio of the halide electrolyte to the composite coating layer is 100:(0.3-0.5).

[0013] In a second aspect, the present application further provides a method for preparing the solid electrolyte as described in the first aspect, characterized in that it comprises the following steps:

[0014] 1) In an inert atmosphere, lithium chloride, zirconium chloride and indium chloride are mixed and co-fired to obtain a halide electrolyte;

[0015] 2) Under an inert atmosphere, alumina and lithium fluoride are subjected to ball milling mixing to obtain a composite coating layer;

[0016] 3) Under an inert atmosphere, performing an atomic layer deposition coating treatment on the halide electrolyte and the composite coating layer to obtain an electrolyte precursor;

[0017] 4) Under an inert atmosphere, performing a low-temperature heat treatment on the electrolyte precursor to obtain the solid electrolyte.

[0018] In a possible implementation, the mixing and co-firing of lithium chloride, zirconium chloride and indium chloride to obtain a halide electrolyte specifically includes:

[0019] 1) High-speed dispersion mixing of lithium chloride, zirconium chloride and indium chloride after powder refinement according to a stoichiometric ratio to obtain a first mixture;

[0020] 2) heat treating the first mixture to obtain a second mixture;

[0021] 3) performing air flow grinding on the second mixture to obtain the halide electrolyte.

[0022] In a possible embodiment, the powdering speed of the powdering and refining treatment is 25000 r / min, the number of powdering times is (4 to 10) times, and the powdering time for each time is (20 to 60) s; and / or, the mixing speed of the high-speed dispersion mixing is (2000 to 4000) r / min, and the mixing time is (1 to 4) h; and / or, the temperature rise rate of the heat treatment is (1 to 2) °C / min, the sintering temperature is (250 to 500) °C, and the insulation time is (6 to 10) h; and / or, the pulverizing nozzle pressure of the airflow grinding treatment is (0.3 to 0.4) MPa, and the feeding nozzle pressure is (0.6 to 0.7) MPa.

[0023] In a possible implementation, the performing of an atomic layer deposition coating process on the halide electrolyte and the composite coating layer to obtain an electrolyte precursor specifically includes:

[0024] 1) Introducing the vapor of the halide electrolyte and the vapor of the composite coating into the reaction chamber simultaneously under the argon gas, and maintaining the vapor for (30 to 90) seconds;

[0025] 2) Purge the reaction chamber with argon gas, and introduce oxygen source vapor into the reaction chamber under the argon gas, and maintain it for (30 to 90) seconds.

[0026] In a possible implementation manner, the deposition temperature of the atomic layer deposition coating process is (100-250)° C., and the deposition pressure is (30-80) torr.

[0027] In a possible embodiment, the ball-to-material ratio of the ball milling mixing treatment is (10-40):1, the ball milling speed is (50-200) r / min, the turntable speed is (1-12) r / min, and the ball milling time is (2-8) h; and / or, the heat treatment temperature of the low-temperature heat treatment is (120-250) °C, the temperature rise rate is (1-2) °C / min, the insulation time is (6-12) h, and the temperature drop rate is (1-2) °C / min.

[0028] In a third aspect, the present application further provides a battery, comprising a positive electrode sheet and a negative electrode sheet, wherein the electrolyte layer in the positive electrode sheet comprises the solid electrolyte as described in the first aspect above.

[0029] In a fourth aspect, the present invention further provides an electrical device, comprising the battery as described in the third aspect above.

[0030] The implementation of the present invention has at least the following beneficial effects:

[0031] 1) The solid electrolyte of the present invention comprises a halide electrolyte and a composite coating layer arranged on the surface of the halide electrolyte, wherein the composite coating layer comprises uniformly mixed aluminum oxide and lithium fluoride, and the mass ratio of the two is (1-9):(9-1); by uniformly coating the surface of the halide electrolyte with high ionic conductivity with a composite coating layer of lithium fluoride and aluminum oxide with a suitable ratio, the solid electrolyte is achieved to have a high ionic conductivity level while having a high oxidation potential and high air stability, which is conducive to achieving high-rate charge and discharge performance of the battery. DETAILED DESCRIPTION

[0032] Here, exemplary embodiments will be described in detail. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present application. Instead, they are only examples of devices and methods consistent with some aspects of the present application as detailed in the attached claims.

[0033] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0034] An embodiment of the present application provides a solid electrolyte, comprising a halide electrolyte and a composite coating layer disposed on the surface of the halide electrolyte, wherein the composite coating layer comprises aluminum oxide and lithium fluoride in a mass ratio of (1 to 9): (9 to 1).

[0035] Exemplarily, the solid electrolyte of the embodiment of the present invention has a core-shell structure, that is, the core material is a halide electrolyte, and the halide electrolyte as the core material itself has a relatively high oxidation potential; at the same time, the core-shell material is a composite coating layer including uniformly mixed aluminum oxide and lithium fluoride, and the lithium fluoride and aluminum oxide in the composite coating layer have a certain ionic conductivity, wherein the mass ratio of lithium fluoride to aluminum oxide in the composite coating layer is (1-9):(9-1), for example, (4:6), (5:5), (6:4), (7:3), (8:2), (9:1) or a range consisting of any two of them, that is, aluminum oxide with good water resistance and lithium fluoride with certain hydrophobicity are used as materials in the composite coating layer, and are uniformly coated on the halide electrolyte particles. After the surface is coated, the solid electrolyte can have a higher ionic conductivity, which is more conducive to achieving high-rate charge and discharge performance of the battery; at the same time, halide electrolytes and oxide materials with higher oxidation potentials are selected as core and core-shell materials respectively, which can effectively ensure that the solid electrolyte has a higher oxidation potential, effectively reduce the side reactions between the solid electrolyte and the positive electrode material, and improve the capacity of the positive electrode active material, thereby improving the battery energy density and cycle stability; in addition, aluminum oxide with good water resistance and lithium fluoride with certain hydrophobicity are selected as the materials of the composite coating layer. After uniformly coating the surface of the halide electrolyte particles, the water resistance of the solid electrolyte can be effectively improved, the harsh environmental requirements for the preparation of the solid electrolyte can be reduced, and it is conducive to the large-scale preparation of the solid electrolyte.

[0036] According to further research by the inventors, the mass ratio of lithium fluoride to aluminum oxide in the above-mentioned composite coating layer is (1-3):(9-7), for example, (1:9), (2:8), (3:7) or a range composed of any two of them. Alumina with good water resistance and lithium fluoride with certain hydrophobicity are used as the materials in the composite coating layer, and by adjusting and optimizing the mass ratio of the two, the air stability of the solid electrolyte can be effectively improved, thereby reducing the preparation environment requirements and manufacturing costs of the battery used therein, making it easier to achieve large-scale mass production.

[0037] After further research, the above-mentioned halide electrolyte is used as the core material, and the composite coating layer of lithium fluoride and aluminum oxide uniformly mixed is used as the core-shell material. The particle size of the halide electrolyte is larger than the particle size of the composite coating layer, so that the composite coating layer forms a relatively dense coating layer, which is uniformly coated on the particle surface of the halide electrolyte. The good material has good contact with the positive electrode material, and a good coating effect is achieved to ensure the stability between the obtained solid electrolyte and the positive electrode material in the battery in which it is used, thereby affecting the battery performance.

[0038] In order to further achieve a good coating effect between the halide electrolyte and the composite coating layer, while taking into account a higher ionic conductivity, the particle size D50 of the halide electrolyte is (8-15) μm, such as 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm or any two of them, and / or, the particle size D50 of the composite coating layer is (0.05-1) μm, such as 0.05 μm, 0.2 μm, 0.4 μm, 0.6 μm, 0.8 μm, 1 μm or any two of them. Based on the principle that ionic conductivity decreases with decreasing particle size, the halide electrolyte is used as the core material of the electrolyte. If the particle size is too small, the electrolyte ion conductivity is low and it is difficult to achieve uniform coating; if the particle size is too large, it affects the contact between the solid electrolyte and the positive electrode material in the battery to which it is applied, and affects the performance of the positive electrode of the battery. The above-mentioned composite coating layer, as the core-shell material of the solid electrolyte, needs to form a relatively dense composite coating layer while taking into account a certain ionic conductivity. If the particle size is too small, the composite coating layer will be too dense, affecting the electrolyte ionic conductivity and volatility. If the particle size is too large, the composite coating layer will be uneven and the coating effect will not be achieved, affecting the stability of the solid electrolyte and the positive electrode material in the battery in which it is used, and thus affecting the battery performance.

[0039] The crystal structure of the above-mentioned halide electrolyte is a monoclinic crystal structure, and the structural characteristics of the monoclinic crystal are mainly reflected in the shape and size of its unit cell. The monoclinic unit cell is usually in the shape of a rhombus, in which the three sides are of unequal length and the three internal angles are also unequal. This asymmetric structure makes the monoclinic crystal present a unique arrangement in space, so that it has high thermal stability and good electrical conductivity, which in turn makes the prepared solid electrolyte have high ionic conductivity and improves the high-rate charge and discharge performance of the battery.

[0040] The chemical formula of the halide electrolyte is Li 2+x In x Zr 1-x Cl6, that is, the halide electrolyte is a monoclinic LIZC halide electrolyte material after element doping modification. For example, Li2ZrCl6 can be modified by In element doping to obtain Li2+x In x Zr 1-x Cl6, and by adjusting the doping amount, its ionic conductivity can be ≥2.5mS / cm; wherein 0.05≤x≤0.95, preferably 0.6≤x≤0.9, for example, 0.6, 0.7, 0.8, 0.9 or a range consisting of any two thereof, more preferably x=0.75, i.e. Li 2.75 In 0.75 Zr 0.25 Cl6, the ionic conductivity of the prepared solid electrolyte is up to 3mS / cm.

[0041] Furthermore, the mass ratio between the core material of the halide electrolyte and the core-shell material of the composite coating layer is used to judge the coating amount of the solid electrolyte with a core-shell structure, wherein, preferably, the mass ratio between the halide electrolyte and the composite coating layer is (0.3-0.5):100, for example (0.3:100), (0.4:100), (0.5:100) or a range composed of any two of them. Then, by selecting a monoclinic halide electrolyte with a higher ionic conductivity (≥2.5mS / cm) as the core material and a uniform mixture of aluminum oxide and lithium fluoride with a certain ionic conductivity as the core-shell material, the target electrolyte ionic conductivity ≥2mS / cm can be achieved by adjusting and optimizing the ratio and thickness of the coating layer materials, thereby making the prepared solid electrolyte have a higher ionic conductivity and improving the high-rate charge and discharge performance of the battery.

[0042] The present application also provides a method for preparing the above-mentioned solid electrolyte, which includes the following steps: firstly, preparing a monoclinic halide electrolyte Li 2.75 In 0.75 Zr 0.25 Preparation of Cl6 (first precursor), that is, mixing and co-firing lithium chloride, zirconium chloride and indium chloride under an inert atmosphere to obtain a halide electrolyte; then preparation of a composite coating layer (second precursor), that is, ball-milling alumina and lithium fluoride under an inert atmosphere to obtain a composite coating layer; then, under an inert atmosphere, atomic layer deposition coating treatment is performed on the halide electrolyte and the composite coating layer to obtain an electrolyte precursor; finally, under an inert atmosphere, low-temperature heat treatment is performed on the electrolyte precursor to obtain the above-mentioned solid electrolyte.

[0043] In some embodiments, in the process of preparing a halide electrolyte used as the core material in a solid electrolyte, the powdered lithium chloride, zirconium chloride, and indium chloride are first dispersed and mixed at a high speed according to a stoichiometric ratio to obtain a first mixture; the first mixture is heat treated to obtain a second mixture; and the second mixture is subjected to air flow grinding to obtain a halide electrolyte.

[0044] Wherein, the powdering speed of the powdering and refining treatment is 25000 r / min, the number of powdering times is (4-10) times, for example, 4 times, 6 times, 8 times, 10 times or a range consisting of any two thereof, and the powdering time for each time is (20-60) s, for example, 20 s, 40 s, 60 s or a range consisting of any two thereof; and / or, the mixing speed of the high-speed dispersion mixing is (2000-4000) r / min, for example, 2000 r / min, 3000 r / min, 4000 r / min or a range consisting of any two thereof, and the mixing time is (1-4) h, for example, 1 h, 3 h, 4 h or a range consisting of any two thereof; and / or, the temperature rise rate of the heat treatment is (1-2) °C / min, for example, 1 °C / min, 1.5 °C / min , 2°C / min or a range consisting of any two thereof, the sintering temperature is (250-500)°C such as 250°C, 400°C, 500°C or a range consisting of any two thereof, the holding time is (6-10)h such as 6h, 8h, 10h or a range consisting of any two thereof; and / or the pulverizing nozzle pressure for air flow milling treatment is (0.3-0.4)MPa such as 0.3MPa, 0.35MPa, 0.4MPa or a range consisting of any two thereof, the feeding nozzle pressure is (0.6-0.7)MPa, for example 0.6MPa, 0.65MPa, 0.7MPa or a range consisting of any two thereof.

[0045] In some embodiments, during the preparation of the solid electrolyte, the ball-to-material ratio of the ball milling mixing treatment is (10-40):1, for example, (10:1), (20:1), (40:1) or a range consisting of any two thereof, the ball milling speed is (50-200) r / min, for example, 50 r / min, 150 r / min, 200 r / min or a range consisting of any two thereof, the turntable speed is (1-12) r / min, for example, 1 r / min, 5 r / min, 12 r / min or a range consisting of any two thereof, the ball milling time is (2-8) h or a range consisting of any two thereof; and / or, the heat treatment temperature of the low-temperature heat treatment is (120-250) °C or a range consisting of any two thereof, the temperature rise rate is (1-2) °C / min, for example, 1 °C / min, 1.5 °C / min , 2°C / min or a range consisting of any two thereof, the holding time is (6-12)h such as 6h, 8h, 12h or a range consisting of any two thereof, and the temperature drop rate is (1-2)°C / min such as 1°C / min, 1.5°C / min, 2°C / min or a range consisting of any two thereof.

[0046] In some embodiments, in the process of performing atomic layer deposition coating treatment on the above-mentioned halide electrolyte and the above-mentioned composite coating layer to obtain an electrolyte precursor, specifically including: introducing the vapor of the halide electrolyte and the vapor of the composite coating layer into the reaction chamber simultaneously under the carrier of argon gas, and maintaining the time for (30 to 90) s, such as 30s, 60s, 90s or a range consisting of any two thereof; purging the reaction chamber with argon gas, and introducing oxygen source vapor into the reaction chamber under the carrier of argon gas, and maintaining the time for (30 to 90) s, such as 30s, 60s, 90s or a range consisting of any two thereof.

[0047] In the above process, the deposition temperature of the atomic layer deposition coating treatment is (100-250)°C, such as 100°C / min, 200°C / min, 250°C / min or a range consisting of any two thereof, and the deposition pressure is (30-80) torr, such as 30 torr, 50 torr, 80 torr or a range consisting of any two thereof.

[0048] The solid electrolyte prepared by the method of the present invention has high ionic conductivity, high oxidation potential and high air stability. On the one hand, it can effectively reduce the side reactions between it and the positive electrode material, improve the capacity of the positive electrode active material, and thus improve the battery energy density, cycle performance and rate performance; on the other hand, it can effectively reduce the harsh environmental requirements for its preparation, realize conventional dew point dry room preparation, and thus achieve a significant reduction in manufacturing costs and large-scale production; it greatly promotes the mass production process and application of solid electrolytes.

[0049] An embodiment of the present invention also provides a battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte layer located between the positive electrode sheet and the negative electrode sheet, characterized in that the electrolyte layer comprises a solid electrolyte prepared according to the above-mentioned solid electrolyte preparation method. The battery has the advantages corresponding to the above-mentioned solid electrolyte, which will not be repeated.

[0050] The present invention does not strictly limit the positive electrode active material in the positive electrode, and can be a positive electrode active material commonly used in current lithium-ion batteries, such as at least one composite oxide of lithium and metals of cobalt, manganese, nickel, and combinations thereof. Specifically, it can be at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, nickel-cobalt-manganese ternary material, nickel-cobalt-aluminum ternary material, lithium iron phosphate (LFP), lithium nickel manganese oxide, lithium-rich manganese-based material, and the like.

[0051] The present invention does not strictly limit the negative electrode active material in the negative electrode sheet, and can be at least one of the negative electrode active materials commonly used in lithium-ion batteries, such as graphite, hard carbon, soft carbon, mesophase carbon microbeads, silicon-based negative electrode materials (mainly including silicon oxide, silicon-carbon negative electrode), tin-based negative electrode materials (mainly including tin, tin alloy), etc.

[0052] The battery in the embodiment of the present invention may be a lithium-ion battery (such as a lithium-ion power battery), a solar cell, or other new energy storage batteries.

[0053] The present invention does not impose any particular limitation on the method for preparing the battery, and the battery can be prepared by referring to conventional methods in the art.

[0054] For example, in a specific embodiment, a battery can be prepared by the following steps:

[0055] 1) The positive electrode active material, the conductive agent, the binder, the lithium salt and the plasticizer are dispersed in a solvent in a specific mass ratio to form a positive electrode active material layer slurry, and then the positive electrode active material layer slurry is coated on the positive electrode current collector, and the positive electrode sheet is obtained after drying;

[0056] 2) Compounding metallic lithium on the negative electrode current collector to obtain a negative electrode sheet;

[0057] 3) The positive electrode sheet, the electrolyte layer containing a solid electrolyte in the positive electrode sheet, and the negative electrode sheet are assembled in this order to obtain a cell, and the battery is obtained by packaging the cell.

[0058] In the embodiment of the present invention, the battery cell may be packaged with conventional shell materials in the art, and the shell may include, for example, soft packaging materials such as aluminum-plastic film (the battery in this case is a soft-package battery), but is not limited thereto.

[0059] The present invention also provides an electric device, including the above battery. The present invention does not specifically limit the electric device, which can be any electric device including the battery, including but not limited to mobile phones, laptop computers, electric bicycles, electric cars, electric toys, energy storage devices, etc.

[0060] The solid electrolyte provided by the present invention and its preparation method and application will be further described in detail below through specific examples.

[0061] Unless otherwise specified, the reagents, materials and instruments used in the following examples are conventional reagents, conventional materials and conventional instruments in the art and can be obtained commercially. The reagents involved can also be synthesized by conventional methods in the art.

[0062] Example 1

[0063] This embodiment provides a solid electrolyte and a solid battery, and the preparation method thereof is as follows:

[0064] 1. Preparation of solid electrolyte

[0065] 1) Specifically, firstly, a high-speed powdering machine is used to pulverize and refine the raw materials of LiCl, ZrCl4 and InCl3, respectively, at a powdering speed of 25000 r / min, a powdering number of (4-10) times, and (20-60) s / time; a certain amount of refined LiCl, ZrCl4 and InCl3 materials are weighed according to the ratio and put into a mixer for high-speed dispersion and mixing, at a mixing speed of (2000-4000) r / min, and a mixing time of (1-4) h, and a first mixture is obtained after the mixing is completed; a Ma The first mixture is heat treated in a furnace at a temperature rise rate of (1-2) °C / min, a sintering temperature of (250-500) °C, and a holding time of (6-10) h. After natural cooling, a rough electrolyte product, i.e., the second mixture, is obtained. The rough electrolyte product is refined by a jet mill, with a crushing nozzle pressure of (0.3-0.4) MPa and a feed nozzle pressure of (0.6-0.7) MPa. The feed speed and the number of repeated jet milling are adjusted until the particle size reaches the required particle size to obtain a halide electrolyte Li 2.85 In 0.85 Zr 0.15 Cl6.

[0066] 2) In the process of preparing the composite coating layer, 10 g of lithium fluoride and alumina can be placed in a ball mill according to a mass ratio of 1:9. After good sealing, a full-range planetary ball mill is used for low-speed full-range ball milling and mixing. The so-called full-range ball milling means that the ball mill turntable mechanism will make a 360° flip movement while the conventional ball milling method will make the material sink to the bottom and compact, and the problem of continuous interval stopping and scraping of the material can be avoided, so as to achieve sufficient mixing, uniformity and refinement of the materials; the ball-to-material ratio is (10-40):1, the grinding speed is (50-200) r / min, the turntable speed is (1-12) r / min, and the grinding time is (2-8) h.

[0067] 3) Under the protection of argon atmosphere, 10g of halide electrolyte and 0.030g of composite coating layer are weighed respectively according to the ratio, the mass ratio of the composite coating layer to the halide electrolyte, that is, the coating amount is 0.3%, and a powder ALD coating system is used. The deposition temperature is 100-250°C and the deposition pressure is (30-80) torr. Specifically, the first precursor vapor and the second precursor vapor are introduced into the reaction chamber at the same time under the argon gas, and the holding time is (30-90) s; the reaction chamber is purged with argon gas, and the oxygen source vapor is introduced into the reaction chamber under the argon gas, and the holding time is (30-90) s; the reaction chamber is purged with argon gas, and the reaction chamber is purged with argon gas. This cycle is repeated 8 to 12 times to obtain an electrolyte precursor.

[0068] 4) After obtaining the electrolyte precursor, in the process of preparing a solid electrolyte based on the electrolyte precursor, a tubular furnace is used to perform low-temperature heat treatment on the current electrolyte precursor, the argon flow rate is controlled at 2L / min, the heat treatment temperature is (120~250)℃, the temperature rise rate is (1~2)℃ / min, the insulation time is 6~12h, and the temperature drop rate is 1~2℃ / min. After cooling, the target electrolyte product is obtained, that is, the solid electrolyte is obtained.

[0069] 2. Preparation of solid-state batteries

[0070] In an argon glove box, the exposed solid electrolyte and positive electrode active material Li(Ni 0.8 Co 0.1 Mn 0.1 )O2(NCM811) were weighed at a weight ratio of 20:80. They were ground evenly using an agate mortar to produce a composite positive electrode material. 14 mg of the composite positive electrode material, 70 mg of Li 5.4 PS 4.4 Cl 1.6The solid electrolyte is stacked. It is press-formed at a pressure of 360MPa to obtain a positive electrode and a solid electrolyte layer. Next, a piece of aluminum foil is stacked on the positive electrode side, thereby forming a collector on the positive electrode side. Then, on the opposite side of the solid electrolyte layer in contact with the positive electrode, an indium sheet with a thickness and diameter of 200μm and 10mm is placed as a negative electrode material. It is press-formed at a pressure of 80MPa to produce a laminate consisting of a positive electrode sheet, a solid electrolyte layer and a negative electrode sheet, and a solid-state battery is assembled.

[0071] Example 2

[0072] The present embodiment provides a solid electrolyte and a solid-state battery, and the preparation method thereof is basically the same as that of Example 1, except that, in the preparation of the solid electrolyte, in step 3), the mass of the composite coating layer is replaced with 0.035 g, and the mass ratio of the composite coating layer to the halide electrolyte, that is, the coating amount is replaced with 0.35%.

[0073] Example 3

[0074] The present embodiment provides a solid electrolyte and a solid-state battery, and the preparation method thereof is basically the same as that of Example 1, except that, in the preparation of the solid electrolyte, in step 3), the mass of the composite coating layer is replaced with 0.040 g, and the mass ratio of the composite coating layer to the halide electrolyte, that is, the coating amount is replaced with 0.4%.

[0075] Example 4

[0076] The present embodiment provides a solid electrolyte and a solid-state battery, and the preparation method thereof is basically the same as that of Example 1, except that, in the preparation of the solid electrolyte, in step 3), the mass of the composite coating layer is replaced with 0.045 g, and the mass ratio of the composite coating layer to the halide electrolyte, that is, the coating amount is replaced with 0.45%.

[0077] Example 5

[0078] The present embodiment provides a solid electrolyte and a solid-state battery, and the preparation method thereof is basically the same as that of Example 1, except that, in the preparation of the solid electrolyte, in step 3), the mass of the composite coating layer is replaced with 0.050 g, and the mass ratio of the composite coating layer to the halide electrolyte, that is, the coating amount is replaced with 0.5%.

[0079] Example 6

[0080] The present embodiment provides a solid electrolyte and a solid-state battery, and the preparation method thereof is basically the same as that of Example 1, except that, in the preparation of the solid electrolyte, the mass ratio of lithium fluoride to aluminum oxide in step 1) is replaced with 2:8, and correspondingly, in step 3), the mass of the composite coating layer is replaced with 0.045 g, and the mass ratio of the composite coating layer to the halide electrolyte, that is, the coating amount is replaced with 0.45%.

[0081] Example 7

[0082] This embodiment provides a solid electrolyte and a solid battery, and the preparation method thereof is basically the same as that of Example 1, except that, in the preparation of the solid electrolyte, the mass ratio of lithium fluoride to aluminum oxide in step 1) is replaced with 3:7, and correspondingly, in step 3), the mass of the composite coating layer is replaced with 0.045g, and the mass ratio of the composite coating layer to the halide electrolyte, that is, the coating amount is replaced with 0.45%. The preparation method of the solid battery refers to Example 1.

[0083] Comparative Example 1

[0084] This comparative example provides a solid electrolyte and a solid-state battery, and the preparation method thereof is basically the same as that in Example 1, except that, in the preparation of the solid electrolyte provided in this comparative example, step 2) is not performed, that is, the mass of the composite coating layer is replaced with 0 g, and the mass ratio of the composite coating layer to the halide electrolyte, that is, the coating amount is replaced with 0.0%.

[0085] Comparative Example 2

[0086] This comparative example provides a solid electrolyte and a solid-state battery, and the preparation method thereof is basically the same as that of Example 1, except that the mass ratio of lithium fluoride to aluminum oxide in step 1) is replaced with 4:6, and correspondingly, in step 3), the mass of the composite coating layer is replaced with 0.045 g, and the mass ratio of the composite coating layer to the halide electrolyte, that is, the coating amount is replaced with 0.45%.

[0087] Comparative Example 3

[0088] This comparative example provides a solid electrolyte and a solid-state battery, and the preparation method thereof is basically the same as that of Example 1, except that the mass ratio of lithium fluoride to aluminum oxide in step 1) is replaced with 3:7, and correspondingly, in step 3), the mass of the composite coating layer is replaced with 0.06 g, and the mass ratio of the composite coating layer to the halide electrolyte, that is, the coating amount is replaced with 0.6%.

[0089] Test Case

[0090] 1. The following performance tests were performed on the solid electrolytes prepared in the above embodiments and comparative examples.

[0091] 1. Ionic conductivity

[0092] Test method: Weigh 100 mg of solid electrolyte powder, put it in an insulating sleeve with an inner diameter of 10 mm, press it at a pressure of 300 MPa, and perform an AC impedance spectrum test to measure the impedance value of the solid electrolyte. Then test the thickness of the pressurized sheet electrolyte, and calculate the ionic conductivity of the solid electrolyte at room temperature 25°C based on the impedance value, thickness value and area of ​​the sheet by the formula σ=d / (R*S), where σ is the ionic conductivity, unit s / cm; d is the thickness of the sheet, unit cm; R is the impedance value, unit Ω; S is the area of ​​the sheet, unit cm 2 .

[0093] 2. Air stability

[0094] Test method: After the ion conductivity test of the same batch of solid electrolytes is completed as above, 100 mg of solid electrolyte powder is sampled and placed in an environment with a temperature of 25±3℃ and a dew point ≤-55℃ for 6 hours. After the standing period, the ion conductivity of the solid electrolyte is retested and the ion conductivity retention ratio is calculated; if the ion conductivity retention rate is ≥95%, it means that the air stability of this solid electrolyte is relatively high.

[0095] 3. Voltage window test

[0096] Test method: Weigh the solid electrolyte and conductive carbon powder in a weight ratio of 70:30 and grind them evenly using an agate mortar. 5.4 PS 4.4 Cl 1.6 The solid electrolyte is stacked. It is pressed at a pressure of 360MPa and then 5.4 PS 4.4 Cl 1.6 A lithium foil is stacked on the side and pressed at a pressure of 100 MPa. Then, stainless steel collectors are placed on the upper and lower sides of the stack, and collector leads are attached to the collectors. Linear sweep voltammetry is performed with a scan range of 2-5V and a scan rate of 0.1mV / S. A tangent is drawn to the oxidation peak of the test curve, and the intersection with the horizontal axis is the oxidation potential of the solid electrolyte.

[0097] The above test results are shown in Table 1.

[0098] 2. The solid-state batteries prepared in the above embodiments and comparative examples were subjected to the following cycle performance tests.

[0099] The solid-state battery prepared above was subjected to a cycle performance test at 25°C. The test process was as follows: the battery was charged to 4.30V at a constant current at a charge rate of 1C, and then discharged to 2.7V at a discharge rate of 1C. This charge and discharge cycle was repeated 200 times. The discharge capacity Q1 at the first cycle and the discharge capacity Q200 at the 200th cycle were measured. The capacity retention rate Q after 200 cycles was calculated according to the following formula. Capacity retention rate Q = Q500 / Q1*100%. At the same time, the first charge gram capacity C0 and the first discharge gram capacity D0 from 2.7 to 4.3V were recorded respectively, and the first coulomb efficiency was calculated according to D0 / C0.

[0100] The test results of the above values ​​are listed in Table 1.

[0101] Table 1

[0102]

[0103] The following conclusions can be drawn from Table 1:

[0104] 1) It can be seen from Examples 1 to 5 and Comparative Example 1 that, under the condition of keeping 10g of halide electrolyte unchanged, the composite coating layer is added to verify that the ionic conductivity, oxidation potential, and ionic conductivity retention rate after exposure of the solid electrolyte prepared by using only 10g of halide electrolyte are low, and the cycle performance of the corresponding solid-state battery is poor; after adding the composite coating layer, and keeping the ratio (1gLiF:9gAl2O3) in the composite coating layer unchanged, as the coating amount increases, the ionic conductivity of the prepared solid electrolyte increases. The ionic conductivity retention rate after exposure showed a downward trend, the ionic conductivity retention rate after exposure showed a trend of first decreasing and then stabilizing, and the oxidation potential showed a trend of first increasing and then stabilizing. When the coating amount was 4.5%, the ionic conductivity of the prepared solid electrolyte was still at a relatively high level (2.68mS / cm), the oxidation potential reached the highest level (4.35V), the ionic conductivity retention rate after exposure was the highest (92.7%), and the battery performance was the best (1C first week efficiency of 92.5%, discharge capacity of 200.7mAh / g, and capacity retention rate of 89.2% after 200 cycles).

[0105] 2) It can be seen from Examples 6 to 7 and Comparative Examples 1 to 3 that by adjusting the coating material ratio while keeping the coating amount at 4.5% unchanged, it can be verified that: when the coating material ratio is (3gLiF:7gAl2O3), that is, the target electrolyte prepared in Example 7 has the best performance, at which the ion conductivity is 2.85mS / cm, the oxidation potential is 4.36V, and the ion conductivity retention rate after exposure is 97.2%. After exposure, the battery test 1C first week efficiency is 93.4%, the discharge capacity is 205.0mAh / g, and the capacity retention rate of 200 cycles is 98.2%.

[0106] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some or all of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A solid electrolyte, characterized in that The invention comprises a halide electrolyte and a composite coating layer arranged on the surface of the halide electrolyte, wherein the composite coating layer comprises lithium fluoride and aluminum oxide in a mass ratio of (1-9):(9-1).

2. The solid electrolyte according to claim 1, characterized in that The mass ratio of the lithium fluoride to the aluminum oxide is (1-3):(9-7).

3. The solid electrolyte according to claim 1, characterized in that The particle size of the halide electrolyte is larger than the particle size of the composite coating layer.

4. The solid electrolyte according to claim 3, characterized in that The particle size D50 of the halide electrolyte is (8-15) μm; And / or, the particle size D50 of the composite coating layer is (0.05-1) μm.

5. The solid electrolyte according to claim 1, characterized in that The crystal structure of the halide electrolyte is a monoclinic crystal structure.

6. The solid electrolyte according to claim 5, characterized in that The chemical formula of the halide electrolyte is Li 2+ x In x Zr 1-x Cl6, 0.05≤x≤0.

95.

7. The solid electrolyte according to any one of claims 1 to 6, characterized in that The mass ratio of the halide electrolyte to the composite coating layer is 100:(0.3-0.5).

8. A method for preparing a solid electrolyte according to any one of claims 1 to 7, characterized in that: The following steps are involved: 1) In an inert atmosphere, lithium chloride, zirconium chloride and indium chloride are mixed and co-fired to obtain a halide electrolyte; 2) Under an inert atmosphere, alumina and lithium fluoride are subjected to ball milling mixing to obtain a composite coating layer; 3) Under an inert atmosphere, performing an atomic layer deposition coating treatment on the halide electrolyte and the composite coating layer to obtain an electrolyte precursor; 4) Under an inert atmosphere, performing a low-temperature heat treatment on the electrolyte precursor to obtain the solid electrolyte.

9. The method for preparing a solid electrolyte according to claim 8, characterized in that: The mixing and co-firing of lithium chloride, zirconium chloride and indium chloride to obtain a halide electrolyte specifically includes: 1) High-speed dispersion mixing of lithium chloride, zirconium chloride and indium chloride after powder refinement according to a stoichiometric ratio to obtain a first mixture; 2) heat treating the first mixture to obtain a second mixture; 3) performing air flow grinding on the second mixture to obtain the halide electrolyte.

10. The method for preparing a solid electrolyte according to claim 9, characterized in that: The powdering speed of the powdering and refining treatment is 25000r / min, the number of powdering is (4-10) times, and the time of each powdering is (20-60)s; And / or, the mixing speed of the high-speed dispersive mixing is (2000-4000) r / min, and the mixing time is (1-4) h; And / or, the temperature rise rate of the heat treatment is (1-2)°C / min, the sintering temperature is (250-500)°C, and the holding time is (6-10)h; And / or, the pulverizing nozzle pressure of the air flow milling treatment is (0.3-0.4) MPa, and the feeding nozzle pressure is (0.6-0.7) MPa.

11. The method for preparing a solid electrolyte according to claim 8, characterized in that: The step of performing an atomic layer deposition coating process on the halide electrolyte and the composite coating layer to obtain an electrolyte precursor specifically includes: 1) Introducing the vapor of the halide electrolyte and the vapor of the composite coating into the reaction chamber simultaneously under the argon gas, and maintaining the vapor for (30 to 90) seconds; 2) Purge the reaction chamber with argon gas, and introduce oxygen source vapor into the reaction chamber under the argon gas, and maintain it for (30 to 90) seconds.

12. The method for preparing a solid electrolyte according to claim 11, characterized in that: The deposition temperature of the atomic layer deposition coating process is (100-250)°C, and the deposition pressure is (30-80) torr.

13. The method for preparing a solid electrolyte according to any one of claims 8 to 12, characterized in that: The ball-to-material ratio of the ball milling mixing treatment is (10-40):1, the ball milling speed is (50-200) r / min, the turntable speed is (1-12) r / min, and the ball milling time is (2-8) h; And / or, the heat treatment temperature of the low-temperature heat treatment is (120-250)°C, the temperature rise rate is (1-2)°C / min, the insulation time is (6-12)h, and the temperature drop rate is (1-2)°C / min.

14. A battery, characterized in that: It comprises a positive electrode sheet and a negative electrode sheet, wherein the electrolyte layer in the positive electrode sheet comprises the solid electrolyte as described in claims 1-7.

15. An electrical equipment, characterized in that: Comprising the battery of claim 14.

Citation Information

Cited By

  • High-entropy all-solid-state electrolyte and preparation method and application thereof

    CN121355360A

  • Halide solid electrolyte stable in air, preparation method and application thereof

    CN121885740A